PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, PROMOSI DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA HEIKA KOPI KARANGANYAR - Santi, Yanuarita; Purwanto, Edi; Ngaisah, Ngaisah (JURNAL ILMIAH EDUNOMIKA, 2024)
The problem statement in this research is as follows: Is there an effect of Product Quality (X1) on Consumer Satisfaction (Y) at Heika Kopi Karanganyar? Is there an effect of Service Quality (X2) on Consumer Satisfaction (Y) at Heika Kopi Karanganyar? Is there an effect of Promotion (X3) on Consumer Satisfaction (Y) at Heika Kopi Karanganyar? Is there an effect of Price (X4) on Consumer Satisfaction (Y) at Heika Kopi Karanganyar? Is there a simultaneous effect of Product Quality (X1), Service Quality (X2), Promotion (X3), and Price (X4) on Consumer Satisfaction (Y) at Heika Kopi Karanganyar? Among these four variables, which one is the most dominant in influencing Consumer Satisfaction (Y) at Heika Kopi Karanganyar? From the data analysis, the multiple linear regression equation obtained is Y = -0.352 + 0.368 X1 + 0.395 X2 + 0.093 X3 + 0.171 X4. The t-test for Product Quality (X1) on Consumer Satisfaction (Y) shows a calculated t value of 10.894 > t table = 1.980, meaning Ho is rejected, and a significance value of 0.000, indicating a significant effect of Product Quality (X1) on Consumer Satisfaction (Y). The t-test for Service Quality (X2) on Consumer Satisfaction (Y) shows a calculated t value of 7.793 > t table = 1.980, and a significance value of 0.000, meaning Ho is rejected, indicating a significant effect of Service Quality (X2) on Consumer Satisfaction (Y). The t-test for Promotion (X3) on Consumer Satisfaction (Y) shows a calculated t value of 3.446 > t table = 1.980, and a significance value of 0.001, meaning Ho is rejected, indicating a significant effect of Promotion (X3) on Consumer Satisfaction (Y). The t-test for Price (X4) on Consumer Satisfaction (Y) shows a calculated t value of 4.591 > t table = 1.980, and a significance value of 0.000, meaning Ho is rejected, indicating a significant effect of Price (X4) on Consumer Satisfaction (Y). The simultaneous F-test shows a calculated F value of 140.421 > F table = 2.311, meaning Ho is rejected, indicating that Product Quality, Service Quality, Promotion, and Price simultaneously influence Consumer Satisfaction at Heika Kopi. The coefficient of determination test using SPSS shows a value of 0.849, meaning 84.9% of the dependent variable (Consumer Satisfaction (Y)) is influenced by the independent variables (Product Quality (X1), Service Quality (X2), Promotion (X3), and Price (X4)), while the remaining 15.1% is influenced by other factors not examined in this study, such as education, economic background, and others. Keywords: product quality, service quality, promotion, price, consumer satisfaction.